Humour as a symptom of research trends in translation studies - Martínez Sierra, Juan José; Zabalbeascoa Terran, Patrick (MonTi Monografías de Traducción e Interpretación, 2018)
This article is an overview of translation studies applied to the case of humour, divided into four parts, plus an extensive bibliography. The first part goes over humour translation as a relevant object of research and why it is worthy of more academic attention. Humour translation should not be dealt with or looked upon as a strange body within translation studies. Part two is an overview of key contributions to the field, from Spain and elsewhere, covering a considerable number of authors and theories. Part three focuses on promising areas of interest for researchers and illustrates how audiovisual translation is a good instance of dynamism within the field, connecting all this to the rich variety of formats and the importance of technology. Part four sketches the landscape of research methods and theoretical frameworks to signpost possible pitfalls involved when methodologies and theoretical frameworks are not clearly and coherently organised given the complexities of studying humour translation.